Kritik des Antisemitismus in der Gegenwart - Grigat, Stephan (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This volume is dedicated to the reconstruction of antisemitic consciousness and the depiction of the modifications of antisemitic resentment in order to sound out conditions and opportunities for a contemporary critique of antisemitism. Based on Adorno's categorical imperative, the volume combines theoretical analyses with practical considerations on how to combat antisemitism in all its current manifestations. A special focus is placed on Israel-related and Islamist antisemitism. The editor of the volume heads the Centre for Antisemitism and Racism Studies (CARS) in Aachen. With contributions by Markus Baum | Daniel Burghardt | Ingo Elbe | Alex Feuerherdt | Thorsten Fuchshuber | Marlene Gallner | Stephan Grigat | Matthias Küntzel | Florian Markl | Ulrike Marz | Elke Rajal | Samuel Salzborn | Gerhard Scheit